2018
DOI: 10.1080/16549716.2018.1477470
|View full text |Cite
|
Sign up to set email alerts
|

How different contexts of social capital are associated with self-rated health among Lithuanian high-school students

Abstract: Background. Adolescents’ self-rated health is related to a number of sociodemographic and socio-economic factors, health-related behaviors, and their social environment. The impact of the latter is still not well explored. An adolescent’s social environment is represented by the social capital, i.e. social resources that they can access. The relationships between various contexts of social capital (family, neighborhood, peers, and school) and self-rated health among adolescents are still unclear. Objective. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
2
16
0
1
Order By: Relevance
“…The answers were binarized into “high” (strongly agree and agree) and “low” (neither agree nor disagree, disagree, and strongly disagree) social capital [49]. These items have been previously used in the studies examining relationships of social capital and physical activity among adolescents of Turkey [40] and Croatia [42], examining relationships of social capital and self-rated health among adolescents in Serbia [50] and Lithuania [51] and in combined sample of European adolescents [52].…”
Section: Methodsmentioning
confidence: 99%
“…The answers were binarized into “high” (strongly agree and agree) and “low” (neither agree nor disagree, disagree, and strongly disagree) social capital [49]. These items have been previously used in the studies examining relationships of social capital and physical activity among adolescents of Turkey [40] and Croatia [42], examining relationships of social capital and self-rated health among adolescents in Serbia [50] and Lithuania [51] and in combined sample of European adolescents [52].…”
Section: Methodsmentioning
confidence: 99%
“…During their longitudinal study in Brazil, Secretti et al [47] found that persons with lower levels of perceived social cohesion had a higher probability of developing a common mental disorder. Others note strong evidence to support that high levels of individual social capital correlate with fewer mental health challenges [45,48,49] and enhanced well-being [9,50]. However, the relationship between social capital and rates of common mental disorders are mixed and in need of further research [45].…”
Section: Social Cohesion and Its Role In Public Healthmentioning
confidence: 99%
“…For example, high school students living in a neighborhood with higher levels of social cohesion and membership in community organizations showed better self-reported wellbeing in New Zealand (28). Further, it was reported that adolescents aged 14-18 years old who have higher community trust showed better self-rated health in Lithuania, adjusted for individual covariates as well as family and school factors (29). Although community trust and third places are different, it is likely that children with high community social capital may be able to access third places, because third places would be located in the community.…”
Section: Discussionmentioning
confidence: 99%